A step‐by‐step protocol for isolation of murine nucleus pulposus cells - Andrew Bratsman; Greig Couasnay; Florent Elefteriou (JOR Spine, 2019)
Abstract The intervertebral disc (IVD) is composed of three separate tissues with distinct origins and properties. Elucidating changes occurring in these tissues in response to injury or age is paramount to identify new therapies to better manage disc and spine degenerative conditions, including low back pain. Despite their small size and different mechanical load pattern compared to higher species, the use of mouse models represents a cost‐effective and powerful approach to better understand the formation, maintenance, and degeneration of the IVD. However, the isolation of the different compartments of the IVD is complicated by their diminutive size. Here, we describe a simple, step‐by‐step protocol for the isolation of the nucleus pulposus (NP) tissues that can then be processed for further analyses. Analysis from mouse NP tissues shows sufficient quantities of RNAs, purity of the NP fraction, and overall RNA quality for gene expression studies, and reveals no increase in expression of disc degeneration markers, including TNFa, IL1b, and Mmp1 up to 15 months of age in C57BL6 wildtype mice.